Dakwah di Kalangan Gen Z: Faktor yang Mempengaruhi Minat Generasi Muda terhadap Kajian - Firdausi, Ghina Zahidatushalihah; Fadilah, Azizah; Indradi, Lakeisha; Adzra, Haura (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2025)
This research examines the factors influencing Gen Z's attitudes towards Islam. Using a qualitative approach through surveys with a small sample size, it was concluded that the factors influencing the study are internal (such as spiritual needs and the desire for self-improvement) and external (such as the theme's relationship with others, groups, and the appeal of da'wah content in the media). Light, relevant, and visually represented studies are more detailed. Social media is effective in influencing Generation Z, but it also helps people choose their content carefully. Preachers are advised to use communicative, contextual, and creative digital platforms to make Islam more understandable to the younger generation.